PROF. CHAN NGAI WENG WINS URBAN ENVIRONMENTAL MANAGEMENT AWARD IN VIETNAM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 25 April 2016 – Professor Dr. Chan Ngai Weng from the School of Humanities, Universiti Sains Malaysia (USM) once again did the university and country proud when he was awarded the Award for Significant Contribution to Sustainable Urban Development Programme and Urban Development by Vietnam National University in Ho Chin Minh City, Vietnam recently.